Gambaran hasil pemeriksaan faal hemostasis pada penderita Diabetes Melitus tipe-2 (DM-2) di RSUP Sanglah, Bali, Indonesia - Nyoman Pramudita; Ni Kadek Mulyantari (DiscoverSys Inc., 2019)
Background: Diabetes Mellitus Type II (DM-2) is a type of hyperglycemic state which is related to metabolic disorders caused by mutations in several genes. Faal hemostasis is a function of the body that aims to maintain the blood that has been thinned so that the blood flowing in the veins and could be interfere with blood glucose level. This study aims to describe the faal hemostasis examination in patients with DM-2 in Sanglah Hospital.Methods: A cross-sectional study was conducted among patients with diabetes mellitus type II (DM-2) who were hospitalized in Sanglah hospital at the period started from January 1st to December 31st, 2015. The sample selection were using consecutive sampling with a total of twenty eight samples. Data were analyzed using SPSS version 17 for WindowsResults: The study found that males were predominant in this study (53.6%). In addition, 51-60 years age group were also predominant (39.3%), following by history of hypertension (82.1%), 10-14 seconds of Prothrombin Time (PT) (67.9%), 30-40 seconds of Activated Partial Thromboplastin Time (APTT) (53.5%), and bleeding time (BT) > 1.3 minutes (67.9%).Conclusion: Several faal hemostasis assessments were predominant in patients with DM-2 such as 10-14 seconds of PT, 20-40 seconds of APTT, and bleeding time more than 1.3 minutes.